Persistent pollutants and the developing brain: the role of PFAS in neurodevelopmental disorders - Lagostena, Laura; Magnelli, Valeria; Rotondo, Davide; Dondero, Francesco (Frontiers in Cellular Neuroscience, 2025)
Per- and polyfluoroalkyl substances (PFAS) are a diverse class of highly persistent organofluorine compounds, and extensively used in industrial and consumer application. Their environmental ubiquity and bioaccumulation in humans have raised concerns about potential health impacts, particularly on neurodevelopment. This mini-review synthesizes epidemiological and experimental research published between 2020 and 2025 examining prenatal PFAS exposure and neurodevelopmental outcomes in children. Prospective birth cohort studies from Europe, North America, and Asia report subtle but statistically significant associations between higher maternal PFAS levels and a range of neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), cognitive delays (e.g., reduced IQ, language impairments), and behavioral dysregulation. Mechanistic investigations reveal that PFAS can cross the placenta, alter maternal–fetal thyroid and sex-steroid hormone homeostasis, activate inflammatory pathways (e.g., AIM2 inflammasome), disrupt neurotransmitter systems (notably dopaminergic and GABAergic signaling), modulate fetal metabolomic profiles, and induce durable epigenetic modifications. Key methodological challenges include heterogeneity of PFAS mixtures, reliance on single-time-point exposure assessments, variable confounder control (e.g., socioeconomic status, maternal IQ, nutrition, breastfeeding), limited follow-up into later childhood or adolescence, and sparse data on emerging short-chain PFAS analogs. To strengthen causal inference and inform public health interventions, future research should employ longitudinal designs with repeated biomonitoring, standardized neuropsychological assessments, advanced mixture-modeling approaches, comprehensive confounder adjustment, inclusion of vulnerable populations, and focused evaluation of replacement PFAS. Coordinated efforts bridging epidemiology, mechanistic science, and regulatory policy are essential to mitigate PFAS exposure and safeguard neurodevelopmental health in future generations.